Strategic Organizational Performance in Electric Power Company in Indonesia - Rio Afrianda; Veithzal Rivai Zainal; Indra Siswanti; Lenny Christina Nawangsari (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2023)
The purpose of the research is to analyze the influence of transformational leadership and strategic organizational change management to organizational performance with organizational climate as mediating variable in the electricity state own Enterprises in Indonesia. This is a quantitative non-experiment research and using questionnaire with 1.429 respondents within divisions of PLN Head Quarter, and its subsidiaries and affiliates during October 2021 – January 2022. The analysis process is conducted by SPSS and LISREL. Research has found that transformational leadership style and strategic organizational change management, both separately and together have positive and significant influenceto organizational climatewith variable of strategic organizational change management has more dominant influence. Transformational leadership style, strategic organizational change management and organizational climate both separately and or together have a positive and significant influence to organizational performance, with variable organizational climate has more dominant influence.Leader should create an effective organizational climate to improve the influence of transformational leadership capability and change management to achieving excellent organizational performance. The mediating effect of organizational climate is the novelty/originality of research, which has an important and positive impact to enhance the impact of transformative leadership styles or strategic organizational change management on organizational performance . The study was conducted at a state-owned enterprise. Further research in various industries/enterprises by state-owned and private companies is expected.